Cross-Bioaugmentation Among Four Remote Soil Samples Contaminated With Oil Exerted Just Inconsistent Effects on Oil-Bioremediation - Al-Mailem, Dina M.; Kansour, Mayada K.; Radwan, Samir S. (Frontiers in Microbiology, 2019)
Soil samples were collected from Kuwait, Lebanon, Egypt and Germany, and artificially polluted with 3% (w/w) crude oil. Cross-bioaugmentation was done among them, and the oil-consumption and the constituent communities of hydrocarbonoclastic bacteria were monitored periodically through 6 months. The results showed that cross-bioaugmentation did not bring about reproducible effects on oil-removal in the four soils. After 6 months, oil-removal values reached between 82 and 95 % in most of the samples including the unbioaugmented controls. The numbers of hydrocarbonoclastic bacteria showed significant increases followed by significant decreases during the course of bioremediation also in the unbioaugmented controls. In most cases, the inoculated bacterial taxa failed to colonize the soils, and oil-removal was achieved mainly by the native (autochthonous) soil bacterial communities. those belonged to the genera Mycolicibacterium, Mycobacterium, Xanthobacter, Pseudoxanthomonas, Pseudomonas, Zavarzinia and others. The microbial communities in the four soils also comprised nitrogen fixing bacteria belonging to the genera Gordonia, Rhizobium, Kocuria and Azospirillum. Such diazotrophs are known to enrich the soils with fixed nitrogen and thus, contribute to enhancing the microbiological hydrocarbon-consumption. It was concluded that cross-bioaugmentation leads to unpredictable and inconsistent effects on oil removal. Therefore, it could not beregarded as the technology of choice for oil-bioremediation.